Incorporation of Large Cycloalkene Rings into Alternating Copolymers Allows Control of Glass Transition and Hydrophobicity - Zhang, Jingling (ACS Macro Lett, 2018)
[Image: see text] We previously reported that cyclohexene and bicyclo[4.2.0]oct-1(8)-ene-8-carboxamides undergo efficient ruthenium-catalyzed alternating ring-opening metathesis polymerization (AROMP). Here, we demonstrate that cyclodecene and cyclododecene also function as cycloalkene monomers in the bicyclo[4.2.0]oct-1(8)-ene-8-carboxamide AROMP system, thus enabling the synthesis of linear alternating copolymers with spacers of different lengths, as demonstrated by means of NMR spectroscopy and gel permeation chromatography. The glass transition temperature and hydrophilicity of the alternating copolymers decrease as the length of the spacers increases, as determined by differential scanning calorimetry and water contact angle measurements.